Pengaruh Suhu Dan Lama Fermentasi Terhadap Karakteristik Kedelai Terfermentasi Dalam Tahapan Produksi Sere Kedele - Geatrin Arumsari, Nyoman; Suparthana, Putu; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This research aims to determine the effect of temperature and fermentation time on characteristics of fermented soybean in the sere kedele production and to obtain the temperature and fermentation time that can produce fermented soybeans in the sere kedele production with the best characteristics. This research used a completely randomized design with factorial pattern with two factors namely, fermentation temperature (30?C, 35?C, 40?C) and fermentation time (24 hours, 36 hours, 48 hours). There are 9 treatment combinations, each treatment combination was repeated 2 times so that the number of treatment combinations was 18 esperimental units. The data obtained were analysed by analysis of variance. For the treatment which had a significant effect, it followed by the Duncan test. The results showed that the fermentation temperature and time had a significant effect (P<0,05) on moisture, ash, protein, fat, carbohydrate, the microbe’s number, hedonic for colour and overall acceptance, but no significant effect (P>0,05) on the hedonic for flavour and texture. Temperature of 40?C with a fermentation time 24 hours is the optimum fermentation temperature and time to produce fermented soybean with moisture content 20,83%, ash content 1,28%, protein content 17,96%, fat content 11,89%, carbohydrate content 47,82%, the microbe’s number 9,97log cfu/g, and sensory properties of color, flavour, texture, and overall acceptance were liked.